2015
DOI: 10.1186/s13045-015-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

The Hedgehog pathway as targetable vulnerability with 5-azacytidine in myelodysplastic syndrome and acute myeloid leukemia

Abstract: BackgroundTherapy and outcome for elderly acute myeloid leukemia (AML) patients has not improved for many years. Similarly, there remains a clinical need to improve response rates in advanced myelodysplastic syndrome (MDS) patients treated with hypomethylating agents, and few combination regimens have shown clinical benefit. We conducted a 5-azacytidine (5-Aza) RNA-interference (RNAi) sensitizer screen to identify gene targets within the commonly deleted regions (CDRs) of chromosomes 5 and 7, whose silencing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Previous studies have reported glasdegib inhibition of SMO reduced the expression of key intracellular leukemia stem cell regulators (eg, GLI2) and enhanced cell cycle transit . These results and preclinical evidence that Hh inhibition may sensitize cells to cytarabine or azacitidine provided rationale for evaluating glasdegib in combination with chemotherapeutic agents to reduce resistance and leukemic persistence or progression.…”
Section: Introductionmentioning
confidence: 73%
“…Previous studies have reported glasdegib inhibition of SMO reduced the expression of key intracellular leukemia stem cell regulators (eg, GLI2) and enhanced cell cycle transit . These results and preclinical evidence that Hh inhibition may sensitize cells to cytarabine or azacitidine provided rationale for evaluating glasdegib in combination with chemotherapeutic agents to reduce resistance and leukemic persistence or progression.…”
Section: Introductionmentioning
confidence: 73%
“…2F). High doses of azacitidine like 10 mmol/L used in these studies exert direct cytotoxic effects (20). Because high versus low doses azacitidine could result in differential mechanisms of anticancer effects, with low doses causing sustained alterations in gene expressions of crucial cancer signaling pathways (21), we also tested clinically relevant lower doses of azacitidine and sivelestat.…”
Section: Inhibition Of Hmgb1 Impairs Cell Expansion and Function Of Mmentioning
confidence: 99%
“…Other studies have shown that Hh signaling is essential for the survival and drug resistance of leukemia cells [22, 23]. Interestingly, a recent report has demonstrated that inhibition of the Hh pathway with LDE225 sensitizes AML cells to 5-azacytidine, and a clinical trial based on these results is ongoing [24]. However, there are no reports of the effects and mechanisms of Hh pathway signaling on radiation resistance or the application of inhibitors to AML.…”
Section: Introductionmentioning
confidence: 99%